BaF radical： A promising candidate for laser cooling and magneto-optical trapping - 许亮 魏斌 夏勇 邓联忠 印建平 (Chinese physics B, 2017)
Recently, there have been great interest and advancement in the field of laser cooling and magneto-optical trapping of molecules. The rich internal structure of molecules naturally lends themselves to extensive and exciting applications. In this paper, the radical 138Ba19F, as a promising candidate for laser cooling and magneto-optical trapping, is discussed in detail.The highly diagonal Franck-Condon factors between theX2∑＋1/2and A2∏1/2states are first confirmed with three different methods. Afterwards, with the effective Hamiltonian approach and irreducible tensor theory, the hypertine structure of theX2∑＋1/2state is calculated accurately. A scheme for laser cooling is given clearly. Besides, the Zeeman effects of the upper （ A2∏1/2）andlower（X2∑＋1/2）levels are also studied, and their respective g factors are obtained under a weak magnetic field. Its large g factor of the upper stateA2∏1/2is advantageous for magneto-optical trapping. Finally, by studying Stark effect of BaFin theX2∑＋1/2, we investigate the dependence of the internal effective electric field on the applied electric field. It is suggested that such a laser-cooled BaF is also a promising candidate for precision measurement of electron electric dipole moment.